Intuitionistic set and its relations (Journal of Bangladesh Academy of Sciences, 2025)
We present a brief overview on Intuitionistic sets and its relations which cuts across some definitions, operations, relations and functions on intuitionistic set. In this article, we have shown various operations and their applications using intuitionistic set. We have also seen that relationships can be established using intuitionistic sets, which work similarly to usual relations. Reflexive, Symmetric, Antisymmetric and Transitive relations can be described using intuitionistic set theory, which demonstrated better results than the previous classical set.J. Bangladesh Acad. Sci. 49(2); 287-293: December 2025